WRC Auto Sendirian Berhad: Potential to Survive after Crisis. Issue 2 (September 2019) - Mohammad, Jihad; Quoquab, Farzana
Iskandar Shah, the outlet manager of WRC Auto Sdn Bhd, was an authorized local car dealer who was facing challenges that he never anticipated throughout his working experience. On March 11, 2011, an earthquake and tsunami occurred in Japan and Perodua's main supplier, Daihatsu, was affected seriously by this natural disaster. Later on, Perodua, officially, stopped their production temporarily for Viva and Myvi. The car components were not enough to supply to the Malaysian car producers, which caused a shortage of new cars in the country. The manufacturers in Japan had estimated 3 months to recover their business operations. Iskandar knew that sales of Viva and Myvi would drop and he needed to plan other alternatives to sustain the business during the 3 months' supply shortage. He had to come up with a different strategy while waiting for the supply chain to recover in July 2011.